Devita, Hellman, and Rosenberg's cancer : principles & practice of oncology - DeVita, Vincent T; Lawrence, Theodore S; Rosenberg, Steven A (Wolters Kluwer, 2015)
"Cancer: Principles and Practice of Oncology presents the practicing oncologist with the practical as well as cutting-edge information needed to ensure the best possible care for each individual patient. To ensure a balanced multidisciplinary approach, a surgeon, a medical oncologist, and a radiation oncologist author each of the major treatment chapters. Each of the major treatment sections is preceded by an updated, brief chapter describing the molecular biology of that cancer and the prospects this new information holds for the improved management of cancer patients"--Provided by publisher.
Keywords: nádory; management bolesti; Medical Oncology; Neoplasms; Pain Management; Disease Management; lékařská onkologie; onkologie; management nemoci